The Relationship Between Teachers’ Job Satisfaction and Organizational Silence Perceptions - Demirtaş, Zülfü; Nacar, Davut (Murat TUNCER, 2018)
This research was conducted on 293 school administrators and teachers working in Elazığ city. The main purpose of the study is to reveal the relationship between teachers’ job satisfaction and organizational silence perceptions. "Teacher Job Satisfaction Scale" and "Organizational Silence Scale" were used as the measurement tools. According to the research findings, both job satisfaction and organizational silence perceptions are moderate. The tasks, branches and age variables currently under construction do not cause differentiation of job satisfaction and organizational silence perceptions. While gender does not cause a significant difference between job satisfaction perceptions, organizational silence causes a meaningful difference in perceptions. There was no significant relationship between job satisfaction and organizational silence perceptions. A low level, linear and meaningful relationship was found between dimensions of organizational silence. The Ministry of National Education assigns the employees who are working as teachers within the last five years to the staff of the school administration for a period of four years. This situation may reduce the job satisfaction of the managers, increasing the perceptions and behaviors of the organizational silence.

Bu araştırma Elazığ ilinde görev yapan 293 okul yöneticisi ve öğretmen üzerinde gerçekleştirilmiştir. Araştırmanın temelamacı okul yöneticisi ve öğretmenlerin iş doyumu ile örgütsel sessizlik algıları arasındaki ilişkiyi ortaya çıkarmaktır. Ölçme aracı olarak “Öğretmen İş Doyumu Ölçeği” ve “Örgütsel Sessizlik Ölçeği” kullanılmıştır. Araştırma bulgularına göre katılımcıların hem iş doyumu hem de örgütsel sessizlik algıları orta düzeydedir. Yapılmakta olan görev, branş ve yaş değişkenleri iş doyumu ve örgütsel sessizlik algılarının farklılaşmasına neden olmamamktadır. Cinsiyet,  işdoyumu algılar arasında anlamlı bir farklılığa neden olmazken, örgütsel sessizlik algılarında anlamlı bir farklılığa neden olmaktadır. İş doyumu ile örgütsel sessizlik algıları arasında anlamlı bir ilişki bulunmamıştır. Örgütsel sessizliğin boyutları arasında düşük düzeyli, doğrusal ve anlamlı bir ilişki bulunmuştur. Milli Eğitim Bakanlığı son beş yıl içerisinde öğretmen olarak görev yapmakta olan çalışanları dört yıllık süreyle okul yöneticiliği kadrolarına görevlendirmektedir. Bu durum, yöneticilerin iş doyumunu düşürüyor, örgütsel sessizlik algı ve davranışlarını yükseltiyor olabilir.
Öğretmenlerin İş Doyumu ve Örgütsel Sessizlik Algıları arasındaki İlişki